2021
DOI: 10.12688/f1000research.53970.2
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus in Nepal from 2000 to 2020: A systematic review and meta-analysis

Abstract: Aims: To evaluate the prevalence and risk factors of type 2 diabetes mellitus (T2DM) from 2000-2020 in various parts of Nepal. Methods: PubMed, Embase, Scopus, and Google Scholar were searched using the appropriate keywords. All Nepalese studies mentioning the prevalence of T2DM and/or details such as risk factors were included. Studies were screened using Covidence. Two reviewers independently selected studies based on the inclusion criteria. Meta-analysis was conducted using Comprehensive Meta-Analysis Softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The second largest prevalence of diabetes was found in South East Asia [ 2 ]. The prevalence of diabetes in Nepal was 10% as per systematic review and meta-analysis [ 3 ] which was higher than reported in a study conducted in 2020 [ 4 ]. Hyperglycemia (high blood glucose) is the third highest risk factor for global premature mortality [ 5 ] causing 6.7 million deaths in 2021 [ 2 ].…”
Section: Introductionmentioning
confidence: 97%
“…The second largest prevalence of diabetes was found in South East Asia [ 2 ]. The prevalence of diabetes in Nepal was 10% as per systematic review and meta-analysis [ 3 ] which was higher than reported in a study conducted in 2020 [ 4 ]. Hyperglycemia (high blood glucose) is the third highest risk factor for global premature mortality [ 5 ] causing 6.7 million deaths in 2021 [ 2 ].…”
Section: Introductionmentioning
confidence: 97%
“…5 A systematic review from 2021 based on publications from 2000 to 2020 noted the pooled prevalence of type 2 diabetes mellitus (T2DM) in Nepal at 10% with a higher prevalence observed in studies published between the years 2015 and 2020, which was at 11.24%. 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, the prevalence of predisposing risk factors for major cardiac events, such as diabetes and hypertension, has also been rising. 6,7 Due to these factors, OHCA poses a significant burden on health care in Nepal, and this is estimated to rise as the population ages. 5 If performed within the first few minutes, CPR can increase the chance of survival for an OHCA victim by nearly 2-to 3-fold.…”
Section: Introductionmentioning
confidence: 99%